2017
DOI: 10.1093/mnras/stx765
|View full text |Cite
|
Sign up to set email alerts
|

A hierarchical model for the ages of Galactic halo white dwarfs

Abstract: In astrophysics, we often aim to estimate one or more parameters for each member object in a population and study the distribution of the fitted parameters across the population. In this paper, we develop novel methods that allow us to take advantage of existing software designed for such case-by-case analyses to simultaneously fit parameters of both the individual objects and the parameters that quantify their distribution across the population. Our methods are based on Bayesian hierarchical modelling which i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…The two objects reported in Gianninas et al (2015), J0301-0044 and J1107+4855, with ages and kinematic characteristics of the halo population, are included in our sample. In Si et al (2017), ten halo white dwarfs were proposed, of which only four are in our 100 pc sample (the two previous ones also included in Gianninas et al 2015 plus J1205+550 and J0346+246), being all four of them identified as halo members by our algorithm. This last object is the well-known and intensively studied ultracool white dwarf WD 0346+246 (J0346+2455) (Hambly et al 1997;Oppenheimer et al 2001;Bergeron 2001).…”
Section: Halo White Dwarf Candidatesmentioning
confidence: 81%
See 1 more Smart Citation
“…The two objects reported in Gianninas et al (2015), J0301-0044 and J1107+4855, with ages and kinematic characteristics of the halo population, are included in our sample. In Si et al (2017), ten halo white dwarfs were proposed, of which only four are in our 100 pc sample (the two previous ones also included in Gianninas et al 2015 plus J1205+550 and J0346+246), being all four of them identified as halo members by our algorithm. This last object is the well-known and intensively studied ultracool white dwarf WD 0346+246 (J0346+2455) (Hambly et al 1997;Oppenheimer et al 2001;Bergeron 2001).…”
Section: Halo White Dwarf Candidatesmentioning
confidence: 81%
“…As previously stated (see Section 5.2), one of the major drawbacks of the Toomre criterion (and similar ones) is that, when the radial velocities are unknown, the Galactic velocity components are reduced and a significant fraction of low-speed halo members are missed. This fact can be exemplified by the object J1107+4855 which, classified as a halo member not only by us but also by other studies (Harris et al 2006;Gianninas et al 2015;Si et al 2017), is not included in the Kilic et al (2018) sample due to its moderately low motion, Vtan = 167 km s −1 .…”
Section: Halo White Dwarf Candidatesmentioning
confidence: 88%
“…Statistical analysis of spectroscopy, photometry, and parallaxes can eventually be used to obtain a very accurate estimate of cooling ages (e.g. O'Malley et al 2013;Si et al 2017) for this sample of known white dwarfs.…”
Section: Resultsmentioning
confidence: 99%
“…This can be accomplished using the following algorithm. A similar strategy is employed by Si et al (2016) when they use Monte Carlo samples from the posterior distribution of the age of a number of white dwarfs obtained from separate fits as a Metropolis proposal rule for fitting a hierarchical model for all of their ages.…”
Section: A Flux Ratio Testmentioning
confidence: 99%